South Indian medicinal plants can combat deadly viruses along with COVID-19? - A review. (November 2020) - Divya, Mani; Vijayakumar, Sekar; Chen, Jingdi; Vaseeharan, Baskaralingam; Durán-Lara, Esteban F.
Abstract: SARS-CoV-2 is a causative agent of Coronavirus disease-19 (COVID-19), which is considered as a fatal disease for public health apprehension worldwide. This pathogenic virus can present everywhere. As it is a virus it can extend easily and cause severe illness to humans. Hence, an efficient international attentiveness of plan is necessary to cure and prevent. In this review, epidemic outbreak, clinical findings, prevention recommendations of COVID-19 and suggestive medicinal value of south Indian plant sources have been discussed. Though the varieties of improved approaches have been taken in scientific and medicinal concern, we have to pay attention to the medicinal value of the plant-based sources to prevent these types of pandemic diseases. This is one of the suggestive and effective ways to control the spreading of viruses. In the future, it is required to provide medicinal plant-based clinical products (Masks, sanitizers, soap, etc., ) with better techniques by clinicians to contend the scarcity and expose towards the nature-based medicine rather than chemical drugs. This may be a benchmark for the economical clinical trials of specific plant material to treat the viral diseases in the future. Graphical abstract: Image 1 Highlights: COVID-19 is considered a greater public health threat. In this review focused on the outbreak, symptoms and preventive measures are 2019-nCoV was discussed. A recommendation of natural medicines has been focused previously treated for several viral infections. Some of the South Indian traditional medicinal plants may have the ability to struggle with 2019-nCoV in the future.